Relationship Between Knowledge of Vaginal Discharge and Preventive Behaviors Among Adolescent Girls - Adriati, Febri; Yuliasari, Alfiyana; Sari, Nirma Lidia (Ahmar Metastasis Health Journal, 2025)
One of the common health problems experienced by adolescent girls is vaginal discharge (leukorrhea). Approximately 60–75% of women worldwide have experienced vaginal discharge, and the prevalence among adolescents in Indonesia remains relatively high. This study aimed to examine the relationship between knowledge of vaginal discharge and preventive behaviors among adolescent girls. This study employed an analytical observational design with a cross-sectional approach. The study population consisted of all ninth-grade female students at SMP Negeri 6 Bandar Lampung, totaling 31 students. A total sampling technique was applied, in which the entire population was included as the study sample. Data were collected using a structured questionnaire. The collected data were analyzed using univariate analysis to describe the characteristics of the variables and bivariate analysis to determine the association between knowledge level and preventive behavior using the Chi-square (χ²) test, with a significance level of α = 0.05. The inclusion criteria were ninth-grade female students at SMP Negeri 6 Bandar Lampung who were willing to participate and present during data collection. The exclusion criteria included students who did not complete the questionnaire fully or were absent at the time of the study. The results showed a significant association between the level of knowledge about vaginal discharge and preventive attitudes among adolescent girls, with a p-value of 0.002. Adolescents with low knowledge levels demonstrated suboptimal preventive attitudes, accounting for 22.6%. These findings indicate that knowledge plays a crucial role in shaping preventive attitudes toward vaginal discharge among adolescent girls at SMP Negeri 6 Bandar Lampung. Based on these results, efforts to improve reproductive health knowledge among adolescent girls through continuous and structured health education are strongly recommended. Schools are expected to play an active role in providing reproductive health education through classroom learning activities, health counseling, and school health programs (UKS) in collaboration with healthcare professionals.